2003
DOI: 10.1118/1.1561623
|View full text |Cite
|
Sign up to set email alerts
|

Determining the incident electron fluence for Monte Carlo‐based photon treatment planning using a standard measured data set

Abstract: An accurate dose calculation in phantom and patient geometries requires an accurate description of the radiation source. Errors in the radiation source description are propagated through the dose calculation. With the emergence of linear accelerators whose dosimetric characteristics are similar to within measurement uncertainty, the same radiation source description can be used as the input to dose calculation for treatment planning at many institutions with the same linear accelerator model. Our goal in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
98
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 37 publications
8
98
1
Order By: Relevance
“…The value for the primary electron beam energy (6.3 MeV) is in keeping with the values obtained by other authors ( 3 , 4 , 7 ) generally between 5.7 and 6.5 MeV. The beam radius value obtained (0.05 cm FWHM) is comparatively smaller than the values reported by Pena et al, ( 3 ) Sheikh‐Bagheri and Rogers, ( 4 ) and Keall et al, ( 7 ) where it has been shown to be between 0.1 cm and 0.2 cm.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The value for the primary electron beam energy (6.3 MeV) is in keeping with the values obtained by other authors ( 3 , 4 , 7 ) generally between 5.7 and 6.5 MeV. The beam radius value obtained (0.05 cm FWHM) is comparatively smaller than the values reported by Pena et al, ( 3 ) Sheikh‐Bagheri and Rogers, ( 4 ) and Keall et al, ( 7 ) where it has been shown to be between 0.1 cm and 0.2 cm.…”
Section: Discussionsupporting
confidence: 90%
“…The angular spread of electrons resulting from scatter in air from a narrow collimated beam, for most practical applications, can be approximated by a Gaussian radial distribution. ( 3 , 7 , 8 ) In order for the BEAMnrc ( 9 , 10 ) code to be used to calculate accurate dose distributions, the accelerator model must first be benchmarked. The initial electron energy and full width half maximum (FWHM) of the radius of the initial electron beam incident on the target was varied to find the percentage depth dose, dose profile curves, and output factors that match the hospital‐measured data, providing output factors that match within 1% of measured output factor values.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have achieved good agreement with measurements using Gaussian‐shaped electron beam models 27 , 28 , 29 …”
Section: Methodsmentioning
confidence: 79%
“…In this study, the mean energy of the incident electron beam on the target and the full width at half maximum (FWHM) of the radial intensity distribution were chosen to match the measurement results based upon previously published works 27 , 28 , 29 . The mean energy of the incident electron beam varied from 5.5 to 7.0 MeV in steps of 0.1 MeV.…”
Section: Methodsmentioning
confidence: 99%
“…However, those approaches require sophisticated and precise modeling of all components in the beam delivery systems and running time‐consuming MC simulations. On top of that, the parameters of MC simulations are generally tuned to match the in‐water measurements; (8) when the investigated detector has a different composition from water, it is very likely the MC simulations have to be re‐run for that type of detector. The complexity of MC simulations makes the above approaches difficult to implement for inexperienced users.…”
Section: Discussionmentioning
confidence: 99%